Ennis Franciscan Friary, south transept, south chapel, piscina jamb and arch moulding - O'Donovan, Danielle (My University, 2008)
Jamb and arch moulding of piscina, from intrados, moulding comprises: chamfer, hollow chamfer, quadrant, right-angled rebate, hollow chamfer, chamfer. The hood comprises hollow, free-standing fillet, hollow, chamfer.
Piscina
Keywords: quadrant; Architecture, Gothic -- Ireland; Ennis (Ireland)--Buildings, structures, etc.; Architecture, Franciscan; Late Medieval; hood moldings; moldings, hollow; roll moldings